A Missed Window of Opportunity: Migration Crisis and the EU Borders after 2015 - Klára Semerádová (Romanian Journal of European Affairs, 2023)
The article discusses the state of the European Union after 2015, when overlapping crises led to new challenges for the EU, which entailed new political dynamics. As the migration and asylum policy of the Union developed at varying rates and depths, the whole policy became non-symmetrical and hard to coordinate, hence weak in the event of a crisis. This vulnerability was demonstrated during the peak of the 2015 refugee crisis that shook Europe and its security and led to immigration politics and an array of problems. This article is a conceptual paper that addresses a number of issues coming to light after the height of the crisis, including the external border policy, the European identity, concerns about the limitations of the liberal state, the politicisation and securitisation of migration, the framing of immigrants, and the phenomenon of reversing the securitisation of migration, which primarily affected Central and Eastern Europe. The article seeks to answer several questions that highlight the irony of using liberal norms for exclusionary purposes, and the degree to which identity politics and policymaking may progressively transcend and reshape the limitations of the liberal states in Europe.